Body composition as a predictor of oncological outcome in patients with non-muscle-invasive bladder cancer receiving intravesical instillation after transurethral resection of bladder tumor - Huang, Liang-Kang; Lin, Yu-Ching; Chuang, Hai-Hua; Chuang, Cheng-Keng; Pang, See-Tong; Wu, Chun-Te; Chang, Ying-Hsu; Yu, Kai-Jie; Lin, Po-Hung; Kan, Hung-Cheng; Chu, Yuan-Cheng; Hung, Wei-Kang; et al. (Frontiers in Oncology, 2023)
Introduction: Body status, categorized as sarcopenia or obesity and assessed using body mass index and body composition, affects the outcome of bladder cancer patients. However, studies comparing disease progression, recurrence, or overall survival in patients with non-muscle-invasive bladder cancer (NMIBC) with different body compositions are lacking. Therefore, we conducted a retrospective study to identify the impact of body composition, sarcopenia, and obesity on the oncological prognosis of patients with NMIBC who underwent transurethral resection of bladder tumor (TURBT) with Bacillus Calmette-Guerin (BCG) intravesical instillation (IVI).Methods: